Visitor behavior in littering at the tourist site of alun-alun Kidul Yogyakarta - Natapraja, Dwi; Surahma Asti Mulasari; Try Wahyuni Sukesi (Sean Institute, 2024)
Waste is one of the contributing factors to environmental pollution, accompanied by a decline in the aesthetic quality of the environment. Municipal waste produced worldwide each year is not handled in an environmentally friendly manner. The amount of waste generated per person per day varies widely worldwide, averaging around 0.74 kilograms. Nationally, the issue of waste accumulation is quite high. According to the Ministry of Environment and Forestry (KLHK), Indonesia generated 30.8 million tons of waste in 2021 and 33.8 million tons of waste in 2022. The research objective is to identify the determining factors of visitors' behavior in littering at Alun-alun Kidul Jogja tourist site. The research adopts a quantitative approach with a cross-sectional design. The study population includes all visitors to Alun-alun Kidul Jogja aged over 17 years. The sample size is determined using the Cochran formula, resulting in a sample of 390 individuals. Sampling is conducted using the Accidental Sampling technique, encountering respondents at the research location. Data obtained are analyzed using descriptive statistics and bivariate analysis with the Chi-square test. The results indicate a relationship between age (P-value 0.000), knowledge (P-value 0.000), and attitude (P-value 0.000) towards littering behavior among tourists. However, there is no relationship between gender (P-value 0.132), education level (P-value 0.343), and facility adequacy (P-value 0.948) and littering behavior among tourists. There is a relationship between visitors' behavior in littering and age, knowledge about waste, and attitude towards littering. Therefore, there is a need to increase individual awareness regarding littering behavior, and individuals should be motivated to read and engage with environmental care promotions to avoid littering indiscriminately.